Case report: Life threatening hyponatremia in infants with urinary tract infections: two cases of type III pseudohypoaldosteronism and review of the literature - Carl, Cécile; Dinkelbach, Lars; Mohr, Julia; Perez, Ruy; Vera Lopez, Tobias; Fricke-Otto, Susanne; Niehues, Tim (Frontiers in Pediatrics, 2024)
We describe two female infants at the age of five and six months with urinary tract infections presenting with vomiting and reduced drinking behavior. On laboratory analysis, severe hyponatremia (106 mmol/l and 109 mmol/l) was seen with hyperkalemia and compensated metabolic acidosis.Endocrinological analyses revealed massively increased levels of aldosterone and renin, leading to the diagnosis of type III pseudohypoaldosteronism (PHA). A review of the current literature 2013-2023 revealed 26 type III PHA cases aged up to ten months with reduced drinking behavior, weight loss and/or failure to thrive being the most common clinical presentations. Given the severe presentation of PHA electrolyte measurements in infants with urinary tract infections and/or in infants with congenital anomalies of the kidney and urinary tract (CAKUT) are strongly recommended.